The Effect of Cheese Banana Chips Product Packaging and Price on Consumer Buying Interest (Case Study of Flamboyan MSMs in Gorontalo City) - Ento, Aprilia A.; Wolok , Tineke; Abdussamad, Zulfia K. (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of cheese banana chip product packaging and price on consumer purchase intention at UMKM (MSME) Flamboyan in Gorontalo City. The sampling technique used was non-probability sampling with a total of 96 respondents. The study employed a quantitative approach, with data collected through questionnaires distributed to consumers at UMKM Flamboyan. The data were analyzed using multiple linear regression analysis. The findings indicate that, partially, product packaging has a positive and significant influence on consumer purchase intention, as shown by a t-count of 7.739 > t-table of 1.985 and a significance level of 0.000 0.05. Price also has a positive and significant influence on consumer purchase intention, with a t-count of 2.464 > t-table of 1.985 and a significance level of 0.016 0.05. Simultaneously, both product packaging and price have a positive and significant influence on consumer purchase intention, as indicated by an F-count of 44.735 F-table of 3.09 and a significance level of 0.000 0.05. The R value is 0.490, meaning that 49% of the variation in purchase intention is explained by the model, while the remaining 51% is influenced by other variables not examined in this study.